2007
DOI: 10.1111/j.1444-2906.2007.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth changes in bighand thornyhead Sebastolobus�macrochir off the Pacific coast of northern Honshu, Japan

Abstract: The biomass of bighand thornyhead Sebastolobus macrochir was increased by the high recruitment success of the 1999-2002 year classes off the Pacific coast of northern Honshu, Japan. In this study, the growth of bighand thornyhead was examined over a 9-year period from 1996 to 2004 in this area. The growth of the 1999 year class and the 2000-2002 year classes was reduced at 3 and 2 years old, respectively, while the 1999-2002 year classes were smaller than the 1993-1998 year classes. In 2-, 3-and 4-year-old fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…In the present study, analyses of GLM indicated that the condition of immature bighand thornyhead deteriorated with an increase in depth, and small fish had lower K, HSI, and SCI than larger specimens. The latter result supports our hypothesis (small bighand thornyhead are potentially in poorer condition in the Tohoku area) derived from the previous studies [3][4][5]. It is probable that deeper waters are less favorable and offer a low quality habitat for immature bighand thornyhead because fish condition can be used as an indicator of habitat quality [13] and small fish are subordinate to large fish (dominant individuals).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, analyses of GLM indicated that the condition of immature bighand thornyhead deteriorated with an increase in depth, and small fish had lower K, HSI, and SCI than larger specimens. The latter result supports our hypothesis (small bighand thornyhead are potentially in poorer condition in the Tohoku area) derived from the previous studies [3][4][5]. It is probable that deeper waters are less favorable and offer a low quality habitat for immature bighand thornyhead because fish condition can be used as an indicator of habitat quality [13] and small fish are subordinate to large fish (dominant individuals).…”
Section: Discussionsupporting
confidence: 88%
“…Nutritional status is a particularly important factor for fish condition and for population success because it affects growth, reproduction, and survival. Hattori et al [3][4][5] reported that density-dependent distributional changes occurred in bighand thornyhead during the 2000s (with small fish occurring in deeper waters due to the increase in density of large fish), and that the growth of 2-and 3-yearold fish was reduced by the increase in fish biomass during the 2000s. In the present study, analyses of GLM indicated that the condition of immature bighand thornyhead deteriorated with an increase in depth, and small fish had lower K, HSI, and SCI than larger specimens.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The bathyal site is within the O 2 -depleted zone of the North Pacific (DO < 45 μM; found at water depths from 700 to 1300 m; Ogura 1970;Fontanier et al 2014). Although there is little fishery activity at the bathyal depth, some important fishery resources such as Sebastolobus macrochir is distributed at that depth (e.g., Hattori et al 2007;Sakaguchi-Orui et al 2014), and knowledge of benthic habitats is essential information for understanding the ecology of such fish. It is also important to observe environmental parameters at this depth to understand how intermediate waters change seasonally at the seafloor, because these variations have not been well understood.…”
Section: Seafloor Monitoring and Ctd Sitesmentioning
confidence: 99%